MODELS AND ALGORITHMS FOR OPTIMIZING LEGAL INFORMATION RETRIEVAL IN THE CORPORATE NETWORK OF ACADEMIC LIBRARIES - Urinkulov, Odil; Abdullayev, Murodjon (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
With the rapid growth of information in the global network, the challenges of finding information quickly and easily in a narrow range of fields of study and specialization are increasing. People are constantly looking for information in some form throughout their lives. This is the result of the constant striving of human beings for innovation, efforts to improve personal and professional competencies. One of the main objectives of libraries is to meet people’s needs for information. In short, this process can be called the type of informational support. The main purpose of this research is to develop models and algorithms to optimize the effective search of information about health information in corporate networks. Electronic libraries in the field of jurisprudence serve not only to train personnel in the field of jurisprudence, but also to increase legal literacy in society, to make citizens aware of their rights and obligations, and to prevent them from becoming victims of various frauds. For organizations, it serves as the most important repository of knowledge for their employees to constantly update their legal knowledge, to draw up normative-legal documents, contracts and agreements within the framework of legal requirements. Despite the fact that the field of jurisprudence is one of the most important areas of activity, the provision of scientific information to this field is not sufficiently systematized. Different organizations and institutions store their existing legal literature in the way they choose, and there is no single mechanism for making it available to users, digitizing, classifying, and searching for it. Most library users rate the efficiency of the library by the availability of the necessary literature. A survey of law students and professors was conducted to examine the interest of library users in legal electronic literature and their use. More than 50% of respondents use the electronic library daily, 93% are looking for legal literature, and 50% of participants said it is difficult to find legal literature. Also, all respondents (100%) approved the need to create a single corporate network by pooling electronic resources of higher education institutions providing legal training.